AN ANALYTICAL COMPARISON OF MONASTICISM IN SEMITIC RELIGION - Razzaq, Tayyaba (Advances in Social Sciences Research Journal, 2021)
Monasticism is voluntary sustain and systemic program of self discipline and self denial in which immediate sensual gratifications are renounced in order to attain some valued spiritual or mental state. Monasticism demands to get away from normal sentiment & human emotions particularly to attain spirituality. Purposes of monasticism are to find out the pure inner self, raise above all flaws & human deficiency, spiritual excellence, liberation, and deliverance. The research paper is an approach to show the comparison between the monastic worlds as revealed through the texts of Semitic religious communities. The comparison of monastic text has the potential to yield a large amount of informative facts. In the areas of asceticism, spirituality, and the balance between sacred and routine life, analogies are numerous and propose many avenues of further comparison still waiting to be explored. The research paper is an approach to show the comparison & in- depth analysis of the Babylonian Talmud, Bible and Quran that find literary analogues in the monastic texts, strategies’, historical examples and suggestions. These examples open the door for a reconsideration of the nature of the relationship between Jews and Christians in the ancient world. This article aimed to highlight the main features of ancient monasticism and to share information in Semitic religion regarding hermit, ascetic and monk. Likewise, this paper also focuses on several processes of changes and transformation of monasticism from a negative view to the enlightenment of identity which lead to the development of a normal and stable society.